Intermediate goals of monetary policy and their relationship to the output gap and inflation in Iraq for the period (1990-2015) - Abbas Kazem Jassim Aldami; Zahraa Yousef Abbas Al - Saadi (Iraqi Journal for Administrative Sciences, 2024)
Understanding the behavior of monetary policy is important because it has a significant impact on the level of economic activity. Therefore, the objectives set by the central bank of monetary policy and its strategies to achieve them should be considered. After studying the objectives and strategies, monetary policy behavior can be assessed in the past, Where can monetary policy be heading in the future? This study attempts to assess the relationship between the objectives of the monetary policy and its final objectives, by looking at the output gap, which is one of the determinants of inflation in the future.